1988
DOI: 10.2134/jeq1988.00472425001700020013x
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Metals by Several Soils of the Southeastern United States

Abstract: Metals in municipal and industrial wastes can cause toxicities in plants and Cd can accumulate to concentrations that pose a health hazard for livestock and humans. Therefore, soil properties important in reducing plant availability of metals must be identified. The capacity of a soil to remove metals from solution is one estimate of the effect of that soil on metal availability to plants. Thirty five milliliter volumes of separate solutions of Cd (0.18 mol m−3), Co (0.34 mol m−3), Cr (0.77 mol m−3), Cu (1.10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
14

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 0 publications
3
34
0
14
Order By: Relevance
“…Relatively few studies have been undertaken on this aspect with tropical soils but similar findings have been reported. For example, in a study of trace metals added as aqueous solutions to 21 soils (A, B and C horizons) from the southeastern United States (including ultisols, alfisols and entisols), King (1988) found that, for all horizons, most of the variation in exchangeable Cd, Co, Cu, Ni and Zn was explained by pH. Exchangeable Cr, Pb and Sb were related more to soil texture.…”
Section: Phmentioning
confidence: 99%
“…Relatively few studies have been undertaken on this aspect with tropical soils but similar findings have been reported. For example, in a study of trace metals added as aqueous solutions to 21 soils (A, B and C horizons) from the southeastern United States (including ultisols, alfisols and entisols), King (1988) found that, for all horizons, most of the variation in exchangeable Cd, Co, Cu, Ni and Zn was explained by pH. Exchangeable Cr, Pb and Sb were related more to soil texture.…”
Section: Phmentioning
confidence: 99%
“…Several studies have demonstrated that pH is one of the most important factors in the control of the concentration of these metals in the soil solution (King, 1988). Elliott et al (1986) proposed that under acidic conditions the phenomenon of adsorption is more important in the control of metal bioavailability, while precipitation reactions and complexation have greater influence under neutral and alkaline conditions.…”
Section: Natural and Anthropogenic Factors Affecting The Bioavail-abimentioning
confidence: 99%
“…Os maiores valores de pH e V% e de teores de K e P nas amostras do solo 5 em relação ao solo 6 (Tabela 4) foram decisivas para a formação de dois grupos distintos; esses parâmetros foram posicionados em região similar em relação às amostras do solo 5. Mesmo que os valores de pH acima da neutralidade, observados nas amostras do solo 5, reduz a mobilidade de metais pesados no solo e a contaminação ambiental (HARTER, 1983;KING, 1988;COOK;HENDERSHOT, 1996;AZIZIAN;NELSON, 1998), essa condição pode ser desfavorável ao crescimento de plantas por tornar alguns micronutrientes (principalmente Fe e Mn) menos disponíveis (WALLACE, 1989;PAULETTI et al, 200). Figura 5.…”
Section: Propriedades Físicas E Químicasunclassified